Differentiation of cyclosporin A from isocyclosporin A by liquid chromatography/electrospray ionization mass spectrometry with post‐column addition of divalent metal salt. (27th January 2014) - Cirigliano, Adriana M.; Cabrera, Gabriela M.
<x xml:space="preserve">Abstract</x> RATIONALE Cyclosporin A (CsA) rearranges to its isomer isocyclosporin A (isoCsA) upon acid hydrolysis and also during ionization in the ion source of the mass spectrometer. It has been reported that both compounds could not be differentiated by tandem mass spectrometry (MS/MS) using atmospheric pressure ionization (API) sources and ambiguously differentiated by using other sources. In order to analyze these compounds which are common fungal metabolites, it is relevant to develop a simple method for their differentiation. METHODS CsA and isoCsA were analyzed by liquid chromatography/mass spectrometry (LC/MS) with post‐column addition of metal ion solutions in a quadrupole time‐of‐flight instrument equipped with an electrospray ionization (ESI) source. RESULTS Mass spectra of CsA obtained upon post‐column addition of solutions of Ca(II), Cu(II) and Zn(II) showed complexes between cyclosporin and the metal, including [2CsA + Me]2+ and [CsA–H + Me]+. These complexes were not observed in the spectra of isoCsA. The same results were observed at different metal concentrations. CONCLUSIONS Differentiation via metal complexation in positive ion mode LC/ESI‐MS was performed to simultaneously distinguish CsA and its isomer isoCsA. Copyright © 2014 John Wiley & Sons, Ltd.